2001
DOI: 10.1046/j.1365-2664.2001.00577.x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat preferences of great bustard Otistarda flocks in the arable steppes of central Spain: are potentially suitable areas unoccupied?

Abstract: Summary 1.Great bustards Otis tarda are globally endangered and 50% of the world population now occurs in agro-steppe habitats in Spain. An understanding of the relationship between land use and the species' habitat requirements is necessary to predict the consequences of land-use change on this declining species. 2. A 2-year study of great bustard substrate preferences was conducted in a large region in central Spain where most cereals are still cultivated in a traditional 2-year rotation. 3. Great bustards s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
88
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 27 publications
3
88
0
3
Order By: Relevance
“…There are extensive agricultural landscapes similar to the Crau in several regions of Spain and Portugal where many lowland grassland birds with unfavourable conservation status are still abundant (De Juana & Martínez 1996;Delgado & Moreira 2000;Lane, Alonso & Martín 2001). However, irrigation schemes in these regions are currently reducing the availability of extensive agricultural habitats (Donazar, Negro & Hiraldo 1993;Bignal & McCracken 1996), affecting many grassland species (Suárez, Naveso & De Juana 1997;Lane, Alonso & Martín 2001) including little bustards (De Juana & Martínez 1996).…”
Section:       mentioning
confidence: 99%
See 1 more Smart Citation
“…There are extensive agricultural landscapes similar to the Crau in several regions of Spain and Portugal where many lowland grassland birds with unfavourable conservation status are still abundant (De Juana & Martínez 1996;Delgado & Moreira 2000;Lane, Alonso & Martín 2001). However, irrigation schemes in these regions are currently reducing the availability of extensive agricultural habitats (Donazar, Negro & Hiraldo 1993;Bignal & McCracken 1996), affecting many grassland species (Suárez, Naveso & De Juana 1997;Lane, Alonso & Martín 2001) including little bustards (De Juana & Martínez 1996).…”
Section:       mentioning
confidence: 99%
“…However, irrigation schemes in these regions are currently reducing the availability of extensive agricultural habitats (Donazar, Negro & Hiraldo 1993;Bignal & McCracken 1996), affecting many grassland species (Suárez, Naveso & De Juana 1997;Lane, Alonso & Martín 2001) including little bustards (De Juana & Martínez 1996).…”
Section:       mentioning
confidence: 99%
“…We also compared density estimates for displaying males among three contrasting landscapes of western Sardinia that differ in land-use composition and structure, recent land-use trends and disturbance levels. From available knowledge of habitat preference of the species, we predicted that males' occurrence would be determined by both large-scale landscape features and small-scale habitat characteristics, with densities higher in the landscape with a balance of pasture and cropland cover and low disturbance levels (Lane et al 2001;Suarez-Seoane et al 2002), and predicted lower densities in the more homogeneous landscapes exposed to greater levels of disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that avian species breeding in pseudo-steppes and aggregating in breeding colonies would suffer the most from the current intensification of farming practices (Lane et al, 2001;Catry et al, 2012). The causal link between the decline of such avian species and agricultural changes has been proposed to operate via density-dependent mechanisms, where colony size plays a crucial role (Rodrıguez et al, 2006).…”
Section: Introductionmentioning
confidence: 99%